2016
DOI: 10.1614/wt-d-15-00118.1
|View full text |Cite
|
Sign up to set email alerts
|

Windrow Burning Eliminates Italian Ryegrass (Lolium perenne ssp. multiflorum) Seed Viability

Abstract: Windrow burning is one of several harvest weed seed control strategies that have been developed and evaluated in Australia to address the widespread evolution of multiple herbicide resistance in annual weeds. Herbicide-resistant Italian ryegrass populations are common in the Palouse region of eastern Washington and northern Idaho. Field and greenhouse studies were conducted to evaluate the effects of burning standing stubble and narrow windrows on the survival of Italian ryegrass seed on the soil surface and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…multiflorum and could be effectively used as an IWM control strategy in eastern Washington and northern Idaho. 36 Seeds of L. perenne ssp. multiflorum and A. palmeri were also found to be effectively destroyed by burning wheat and soybean windrows in Virginia.…”
Section: Narrow-windrow Burningmentioning
confidence: 99%
See 1 more Smart Citation
“…multiflorum and could be effectively used as an IWM control strategy in eastern Washington and northern Idaho. 36 Seeds of L. perenne ssp. multiflorum and A. palmeri were also found to be effectively destroyed by burning wheat and soybean windrows in Virginia.…”
Section: Narrow-windrow Burningmentioning
confidence: 99%
“…Conversely, winter annual grasses appear to be better suited for management with HWSC. 8,26,36 Among broadleaf weeds, species such as Erigeron canadensis L. and Taraxacum officinale F. H. Wigg. that disperse seeds by wind prior to harvest are also not good targets for HWSC.…”
Section: Critique Of Hwsc 41 Weed Types/life Cycles Not Effective Fomentioning
confidence: 99%
“…In order to control multiple herbicide‐resistant weed biotypes, agroecologists have developed numerous techniques that intercept and kill weed seeds before they enter the soil [collectively termed harvest weed seed control (HWSC)] . Of all HWSC techniques, narrow windrow burning is the most widely adopted in Australia, requiring growers to capture weed seeds mechanically at harvest and concentrate them into a narrow windrow, 0.7–1 m wide, at the rear of the harvester with the chaff fraction . In the following autumn, these narrow windrows are burnt, achieving sufficient temperatures for sufficient length of time to kill the intercepted weed seeds .…”
Section: Introductionmentioning
confidence: 99%
“…13 Of all HWSC techniques, narrow windrow burning is the most widely adopted in Australia, requiring growers to capture weed seeds mechanically at harvest and concentrate them into a narrow windrow, 0.7-1 m wide, at the rear of the harvester with the chaff fraction. [13][14][15][16] In the following autumn, these narrow windrows are burnt, achieving sufficient temperatures for sufficient length of time to kill the intercepted weed seeds. 13,17 Like weed seeds, S. sclerotiorum sclerotia are commonly found as contaminants in harvested canola seed, indicating that sclerotia located above a harvest cutting height are intercepted during grain harvest.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of post‐harvest residue deposited each year, and the often‐reported negative consequences of residue retention on the soil surface, allow for sugarcane growers to at least partially control weed seed using heat. Many studies have shown successful control of problematic weed seeds in numerous cropping systems across the world using heat (Bolfrey‐Arku et al, 2011; Lyon et al, 2016; Walsh et al, 2017; White and Boyd, 2016). Although few studies have investigated the effect of temperature on itchgrass seed mortality (Bolfrey‐Arku et al, 2011), none has reported on divine nightshade.…”
mentioning
confidence: 99%